The Dark Side of Nrf2 in the Heart - Zang, Huimei; Mathew, Roy Oomen; Cui, Taixing (Frontiers in Physiology, 2020)
Nuclear factor-erythroid factor 2-related factor 2 (Nrf2) is a critical transcription factor which regulates the expression of over 1000 genes in the cell under normal and stressed conditions. These transcripts can be categorized into different groups with distinct functions including antioxidative defense, detoxification, inflammatory responses, transcription factors, proteasomal and autophagic degradation, and metabolism. Nevertheless, Nrf2 has been historically considered as a crucial regulator of antioxidant defense to protect against various insult-induced organ damage and has evolved as a promising drug target for the treatment of human diseases, such as heart failure. However, burgeoning evidence has revealed a detrimental role of Nrf2 in cardiac pathological remodeling and dysfunction towards heart failure. In this mini-review, we outline recent advances in structural features of Nrf2 and regulation of Nrf2 activity, and discuss the emerging dark side of Nrf2 in the heart as well as the potential mechanisms of Nrf2-mediated myocardial damage and dysfunction.